Implementasi Tugas Pokok Dan Fungsi (TUPOKSI) Pada Kantor Pelayanan Perizinan Terpadu Kota Pagar Alam - Kasman Kasman (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to find out how to implement the main tasks and functions of the integrated licensing service office in Pagar Alam City. This type of research is qualitative descriptive research, namely explaining the conditions or facts of findings that occur in the field in a scientific manner with a more in-depth analysis of the main tasks and functions (TUPOKSI) of the Employees of the Integrated Licensing Service Office (KPPT) of Pagar Alam City. There are 6 informants who were determined in this study with a purposive sampling method. Data collection techniques in this study were interviews, documentation and observation. Overall, the main tasks and organizational system functions of the Integrated Licensing Service Office of Pagar Alam City in licensing services have been going well